What we want is what we get Group-based emotional preferences and conflict resolution. [article]. - Porat, Roni
Imagine yourself facing someone who might attack your group-if you could control your emotions, how would you want to feel toward that person? We argue that goals people have for their group dictate how they want to feel on behalf of their group. We further propose that these group-based emotional preferences, in turn, influence how people actually feel as group members and how they react to political events. We conducted 9 studies to test our proposed model. In a pilot study, we showed that political ideology is related to how people want to feel toward outgroup members, even when controlling for how they want to feel in general, or how they actually feel toward outgroup members. In Studies A1-A3, we demonstrated that group-based emotional preferences are linked to emotional experience and that both mediate links between political ideology and political reactions. In Study A4, we showed that political ideology influences emotional preferences, emotional experiences and political reactions. Next, in Studies B!-B4, we demonstrated that changing group-based emotional preferences can be shape group-based emotional experiences and consequently influence political reactions. By suggesting that group-based emotions are motivated, our findings point to new directions for advancing conflict resolution. -- (from the authors)